2022
DOI: 10.1161/circulationaha.122.059971
|View full text |Cite
|
Sign up to set email alerts
|

Detection of G Protein–Coupled Receptor Autoantibodies in Postural Orthostatic Tachycardia Syndrome Using Standard Methodology

Abstract: Background: Postural orthostatic tachycardia syndrome (POTS) is a disorder of orthostatic intolerance that primarily affects women of childbearing age. The underlying pathophysiology of POTS is not fully understood, but it has been suggested that autoimmunity may play a role. The aim of this study was to compare concentrations of autoantibodies to cardiovascular G protein–coupled receptors between patients with POTS and healthy controls. Methods: Sera w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
15
2
1
Order By: Relevance
“…One recent study aimed to measure G protein-coupled receptor autoantibodies in POTS. However, results from this study could not prove that patients with POTS and healthy controls had different autoantibody concentrations for several cardiovascular GPCRs ( 80 ). Autoimmunity has been suggested to play a potential role in the underlying pathophysiology of both POTS and TTS ( 80 , 81 ).…”
Section: Alternative Explanatory Framework For Pathophysiology Of Tts...contrasting
confidence: 62%
See 1 more Smart Citation
“…One recent study aimed to measure G protein-coupled receptor autoantibodies in POTS. However, results from this study could not prove that patients with POTS and healthy controls had different autoantibody concentrations for several cardiovascular GPCRs ( 80 ). Autoimmunity has been suggested to play a potential role in the underlying pathophysiology of both POTS and TTS ( 80 , 81 ).…”
Section: Alternative Explanatory Framework For Pathophysiology Of Tts...contrasting
confidence: 62%
“…However, results from this study could not prove that patients with POTS and healthy controls had different autoantibody concentrations for several cardiovascular GPCRs ( 80 ). Autoimmunity has been suggested to play a potential role in the underlying pathophysiology of both POTS and TTS ( 80 , 81 ). With that in mind, and in the context of orexin-system dysfunction, future studies should assess orexin autoantibodies in both TTS and POTS.…”
Section: Alternative Explanatory Framework For Pathophysiology Of Tts...contrasting
confidence: 62%
“…Antibodies against G‐protein‐coupled cardiovascular receptors have been formerly hypothesized to contribute to POTS pathogenesis [32, 33]. However, more recent studies found positive antibody titers against G‐protein‐coupled cardiovascular receptors also in healthy people [34], questioning their pathogenic role in POTS settings. Interestingly, autoimmune autonomic ganglionopathy, an autonomic disorder mediated by antibodies against the α 3 ‐subunit of the ganglionic nicotinic acetylcholine receptor, was only rarely diagnosed after COVID‐19 infection by the survey responders.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against G-protein-coupled cardiovascular receptors have been formerly hypothesized to contribute to POTS pathogenesis [32,33]. However, more recent studies found positive antibody titers against G-protein-coupled cardiovascular receptors also in healthy people [34], questioning their pathogenic role in POTS settings.…”
Section: Discussionmentioning
confidence: 99%
“…Es especialmente frecuente el anticuerpo contra el receptor alfa-1 adrenérgico, seguido del muscarínico M4 67 . Sin embargo, la especificad de detección de estos anticuerpos por medios convencionales (ELISA) está en entredicho debido a la frecuencia de falsos positivos en pacientes controles 68 .…”
Section: Neuropatías Autonómicas Autoinmunesunclassified